Analisis Wacana Kebijakan Maritim: Studi Kasus Nelayan Pantai Kedonganan Kabupaten Badung Provinsi Bali - Diwyo, Adwitya Aksomo; Noak, Piers Andreas; Ali Azhar, Muhammad (Jurnal Nawala Politika, 2019)
ABSTRACT Maritime sector policy runs into a tidal condition until President Joko Widodo attempted to exploit one of the power sources of Indonesia through maritime policy discourse, aiming Indonesia as the world's maritime axis. Factually, the implementation of maritime policy discourse encounter obstacles and seems going nowhere caused by the focus of government in national infrastructure development and facing unoptimized condition. This research using Foucault's discourse analysis. Data found that the media contributes to deploy the maritime policy discourse and the realization of maritime policies to Kedonganan fishermen yet unoptimized as discovered that the policies been less prosperous in generally. Those policies formed into sailing operational aid and fishermen insurance facing an unoptimized target. Based on those results, the conclusions drawn into the actualization of maritime policies particularly for coastal fishermen tend to be less effective in a regulation side and less prosperous for the Kedonganan fishermen in general because of an unoptimized target. Keywords: Discourse, Maritime Policy, Media, Kedonganan Fishermen.